Demand Response Management in Smart Homes Using Robust Optimization. Issue 8 (8th May 2020) - Mahmoudi, Mojtaba; Afsharchi, Mohsen; Khodayifar, Salman
Abstract : Abstract—Shortage of nonrenewable energy resources, the pollution arising from extraction and exploitation of these resources, and increasing demand for energy, along with the intermittent nature of renewable resources have resulted in more attention to demand response programs in smart grids. Demand response includes activities like load management, energy efficiency, and energy saving. The residential sector plays a significant role in achieving demand response goals. Home energy management systems shift or restrict a household demand; they consider power price and consumer's wellbeing and improve consumption and production profile of a house. In this work, a price-based, real-time demand response management model is proposed as a home energy management system. The model helps conservative householders save energy and improve energy efficiency through managing electrical appliances. The proposed model can be embedded in an energy control unit or a smart meter and find the optimal operation of the house for next 5 minutes via robust optimization technique, considering uncertainties of power price and distributed generation. The objective is to minimize the electricity costs of a home and improve the role of distributed generation and energy storage system installed inside the home while satisfying user's wellbeing and components constraints. The model is comprehensive, real-time, have high time resolution, and the results show that the model improves the costs of a conservative household.